ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU SMA NEGERI 4 KOTA JAMBI - Syachroni . (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
This study aims are: (1) Determine an overview of the motivation, ability, role perceptions and situational organization and performance of teachers SMAN 4 Jambi. (2) Determine the influence of motivation, ability, role perceptions and situational organization on teacher performance SMAN 4 Jambi. (3) Analyze the factors that affect the performance of teachers SMAN 4 Jambi. (1) The results showed that the average score of five variables situational variables that organizations obtain the mean score of the high category, while the other four variables (X1, X2, X3) in the medium category. (3) the results of the t test is known that the motivation factor (X1) with a probability value (sig) 0.000 <0.05; ability (X2) with probability value 0.008 <0.05, and situational organization (X4) have a significant effect on performance (Y). While the perception of the role (X3) with probability 0.269> 0.05 no significant effect on performance(Y). Keywords: Teacher Performance; Motivation; Ability; RolePerception; SituationalOrganization Â